Pengaruh Kepemimpinan Kepala Sekolah, Iklim Sekolah dan Motivasi Berprestasi Terhadap Komitmen Guru di Smk Canda Bhirawa Pare - Fadoli, Moh (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
This study was carried out at SMK Canda Bhirawa Pare with the objective of identifying and analyzing the significant impact of principal leadership, school climate, and achievement motivation on teacher commitment, both individually and collectively. Data collection was done through field surveys using questionnaires distributed to all 110 teachers. A quantitative approach was used with saturated sampling to select the sample. The data underwent validity and reliability tests, as well as classical assumption tests such as normality, heteroscedasticity, and multicollinearity. The analysis was performed using multiple linear regression, supported by SPSS 26 software. The sampling method applied was saturated sampling or census, where 85 teachers with at least one year of experience were chosen from the total of 110 teachers using purposive sampling. The results of the research reveal that the variables of principal leadership and achievement motivation have a positive and significant effect on teacher commitment, both individually and collectively. However, the school climate variable does not have an impact on teacher commitment at SMK Canda Bhirawa Pare.